2020
DOI: 10.3389/fpsyt.2020.550593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Supplementation on Gastrointestinal, Sensory and Core Symptoms in Autism Spectrum Disorders: A Randomized Controlled Trial

Abstract: The microbiota-gut-brain axis has been recently recognized as a key modulator of neuropsychiatric health. In this framework, probiotics (recently named "psychobiotics") may modulate brain activity and function, possibly improving the behavioral profiles of children with Autism Spectrum Disorder (ASD). We evaluated the effects of probiotics on autism in a double-blind randomized, placebo-controlled trial of 85 preschoolers with ASD (mean age, 4.2 years; 84% boys). Participants were randomly assigned to probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 51 publications
6
131
0
4
Order By: Relevance
“…Ten of them provided information on sex ratio of subjects with ASD (predominantly male). Most studies ( n = 10) documented the presence of at least one comorbid condition in their study cohort, primarily GI symptoms (Arnold et al, 2019; Grimaldi et al, 2018; Inoue et al, 2019; Kang et al, 2017; Niu et al, 2019; Sanctuary et al, 2019; Santocchi et al, 2020; Shaaban et al, 2018; Wang et al, 2020; West et al, 2013). Only five studies monitored participant compliance (Arnold et al, 2019; Grimaldi et al, 2018; Sanctuary et al, 2019; Santocchi et al, 2020; Shaaban et al, 2018), of which three reported their assessment results (high compliance rates [> 90%]) (Arnold et al, 2019; Sanctuary et al, 2019; Santocchi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten of them provided information on sex ratio of subjects with ASD (predominantly male). Most studies ( n = 10) documented the presence of at least one comorbid condition in their study cohort, primarily GI symptoms (Arnold et al, 2019; Grimaldi et al, 2018; Inoue et al, 2019; Kang et al, 2017; Niu et al, 2019; Sanctuary et al, 2019; Santocchi et al, 2020; Shaaban et al, 2018; Wang et al, 2020; West et al, 2013). Only five studies monitored participant compliance (Arnold et al, 2019; Grimaldi et al, 2018; Sanctuary et al, 2019; Santocchi et al, 2020; Shaaban et al, 2018), of which three reported their assessment results (high compliance rates [> 90%]) (Arnold et al, 2019; Sanctuary et al, 2019; Santocchi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The selected articles reported on 13 different interventional studies that examined the use of microbial‐based therapies for the treatment of children with ASD. Eight probiotic trials were identified, of which two evaluated the effect of administering a single probiotic strain (Liu, Liong, et al, 2019; Parracho et al, 2010), while six investigated multiple probiotic strains in combination (Arnold et al, 2019; Liu, Liong, et al, 2019; Santocchi et al, 2020; Shaaban et al, 2018; Tharawadeephimuk et al, 2019; West et al, 2013). These interventions were primarily Bifidobacterium , Lactobacillus , and Lacticaseibacillus based; the most commonly tested strains were Bifidobacterium longum ( n = 5) and Lactobacillus acidophilus ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a specific species of Bacteroidetes called Bacteroidetes fragilis (B. fragilis) was shown to improve gut integrity and reduce ASD behavioral symptoms such as anxiety and repetitive behavior when it was administrated in ASD induced mice [ 123 ]. The administration of probiotics seems to be beneficial for ASD patients, as it has been explored in clinical trials (NCT02708901), and it showed a positive impact on ASD core symptoms in a subset of ASD patients [ 124 ].…”
Section: Metabolomics and Gut Microbiome’s Biomarkers In Asdmentioning
confidence: 99%
“…The ef icacy of probiotics as a treatment option to suppress GI symptoms in ASD affected individuals was demonstrated through a randomized controlled study by Santocchi et al (2020). The study involved 85 participants diagnosed with ASD, who were randomly given probiotic or placebo mixture for six months.…”
Section: Figure 4: Microbial Dysbiosis and Its Effect In Asdmentioning
confidence: 99%